(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The process of wheat grain ripening is accompanied by significant physiological and biochemical changes, among which the state and distribution of water play a crucial role. This study investigates the dynamics of water content, its binding forms, and spatial distribution within wheat grains at different stages of maturation. During early developmental stages, grains contain a high proportion of free water, which ensures active metabolic processes, cell division, and nutrient transport. As ripening progresses, the total moisture content decreases, and water gradually transitions into bound forms associated with macromolecules such as proteins, starch, and cell wall components. This shift contributes to structural stabilization and prepares the grain for storage and dormancy. The distribution of water within grain tissues—endosperm, embryo, and outer layers—becomes increasingly heterogeneous, reflecting differences in biochemical composition and metabolic activity. The reduction of free water and increase in bound water are essential for improving grain quality, resistance to mechanical damage, and long-term preservation. Understanding these processes provides important insights for optimizing harvesting time, storage conditions, and processing technologies in agriculture.